2017
DOI: 10.1111/jpn.12839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chestnut tannins on intestinal morphology, barrier function, pro‐inflammatory cytokine expression, microflora and antioxidant capacity in heat‐stressed broilers

Abstract: A study was conducted to evaluate the effects of chestnut tannins (CT) on intestinal morphology, barrier function, pro-inflammatory cytokine expression, microflora and antioxidant capacity in heat-stressed broilers. Four hundred 28-day-old male Ross 308 broilers were randomly assigned into four groups, with 10 replicates per group and 10 broilers per replicate. The broilers in the normal (NOR) group were kept at 22 ± 1°C and fed the basal diet, and each of the other three groups were treated with cyclic heat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…The pro‐inflammatory cytokines, such as LITAF (similar to TNF‐α in mammals), produced during the inflammatory process induced by infectious factors can disrupt the intestinal tight junction barrier (Al‐Sadi, Guo, Ye, Rawat, & Ma, ). Our result also showed that heat stress increased the pro‐inflammatory cytokine expression, specifically, the expression of LITAF in the jejunum of chickens, which enhanced the intestinal permeability and damaged mucosal barrier; which agreed with previous reports (Liu et al, ). Emerging evidence confirmed that the NF‐κB is a central regulator of inflammation, innate immunity and intestinal barrier function (Nenci et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The pro‐inflammatory cytokines, such as LITAF (similar to TNF‐α in mammals), produced during the inflammatory process induced by infectious factors can disrupt the intestinal tight junction barrier (Al‐Sadi, Guo, Ye, Rawat, & Ma, ). Our result also showed that heat stress increased the pro‐inflammatory cytokine expression, specifically, the expression of LITAF in the jejunum of chickens, which enhanced the intestinal permeability and damaged mucosal barrier; which agreed with previous reports (Liu et al, ). Emerging evidence confirmed that the NF‐κB is a central regulator of inflammation, innate immunity and intestinal barrier function (Nenci et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Heat stress caused an increase in intestinal permeability that was associated with an decrease in claudin‐1 expression (Dokladny et al, ). These results demonstrated that heat stress impaired the gut morphology and increased the intestinal permeability in chickens (Liu et al, ; Song et al, ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, it is believed that hydrolysable tannins have a positive role in growth performance and health status in chickens ( Schiavone et al., 2008 ). Hydrolysable tannic acid is made from wood extract that has higher polyphenolic compounds ( Kumar and Vaithiyanathan, 1990 ; Liu et al., 2018 ). Supplementation of tannins could improve the body weight gain in rabbits ( Liu et al., 2012 ) and broilers ( Dong et al., 2015 ; Xiong et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2009) found that supplementation of 250 or 500 mg/kg chestnut tannins had no significant effects on body weight gain and feed-to-gain ratio, whereas 1,000 mg/kg diets reduced the final body weight in broilers. Furthermore, chestnut tannins could improve intestinal morphology, cytokine expression, and antioxidant activities in broilers ( Liu et al., 2018 ). Dietary supplementation of chestnut wood extract (CWE) as hydrolysable tannins could reduce carcass fat deposition and water-holding capacity of meat and increase polyunsaturated fatty acids in fat tissues of pigs ( Rezar et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%